LEVANTAMENTO DE INJÚRIA MECÂNICA EM BANANA PRATA ANÃ DURANTE O TRANSPORTE - Costa, Franciscleudo Bezerra da; Puschmann, Rolf; Moreira, Silvino Intra; Ribeiro Junior, José Ivo; Luiz Finger, Fernando (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2010)
Banana sold in the internal Brazilian market has low quality due to the presence of bruises spots spread all over the skin. In this work, the purpose was to evaluate the mechanical injury intensity in Prata Anã bananas as related to packaging type, at harvesting and during postharvest handling steps. Fruits were harvested at green unripe stage from a commercial plantation in Janaúba-MG, in July and in November 2003, and were transported to Viçosa-MG, about 800 km far way, packed in wood crates ‘torito’ + cardboard, ‘plastic’ and ‘cardboard’ boxes. Regardless the season of harvest, at least 93% of the fruits showed some kind mechanical wounding on the skin after shipping. But, the total surface skin area damaged was significantly higher during the month of November (spring) compared to July (winter) for all three different boxes. Bananas shipped inside cardboard boxes had larger wounding areas compared to ‘torito’ + cardboard and plastic boxes. Among the postharvest handling steps, which included, harvest, transport by aerial cable, preparation of finger and shipping, the last was most damaging to the fruit surface. However, the extent of wounding imposed to the fruits after had been shipped, did affect the course of ripening.